Аппроксимационные свойства систем экспонент в одном пространстве аналитических функций - Винницкий, Б.В. (Український математичний журнал, 1996)
We obtain a criterion of completeness of a system of exponentials in the Hardy-Smirnov spaces in unbounded convex polygons and study the properties of incomplete systems of exponentials.